2017
DOI: 10.7554/elife.23608
|View full text |Cite
|
Sign up to set email alerts
|

Threat of shock increases excitability and connectivity of the intraparietal sulcus

Abstract: Anxiety disorders affect approximately 1 in 5 (18%) Americans within a given 1 year period, placing a substantial burden on the national health care system. Therefore, there is a critical need to understand the neural mechanisms mediating anxiety symptoms. We used unbiased, multimodal, data-driven, whole-brain measures of neural activity (magnetoencephalography) and connectivity (fMRI) to identify the regions of the brain that contribute most prominently to sustained anxiety. We report that a single brain regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 150 publications
(250 reference statements)
5
38
0
Order By: Relevance
“…Previous studies using electroencephalography (EEG) have demonstrated hyperactivity in the parietal cortex as a function of arousal in anxious patients 12 , suggesting a potential link between parietal hyperactivity and attention control deficits 13 . Consistent with these results, our previous work used unbiased data-driven approaches in a multimodal (MEG/fMRI) neuroimaging study of effects of threat-of-shock-induced anxiety on cortical excitability (alpha desynchronization) and global brain connectivity 14 .…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…Previous studies using electroencephalography (EEG) have demonstrated hyperactivity in the parietal cortex as a function of arousal in anxious patients 12 , suggesting a potential link between parietal hyperactivity and attention control deficits 13 . Consistent with these results, our previous work used unbiased data-driven approaches in a multimodal (MEG/fMRI) neuroimaging study of effects of threat-of-shock-induced anxiety on cortical excitability (alpha desynchronization) and global brain connectivity 14 .…”
Section: Introductionsupporting
confidence: 60%
“…We based our target choice on group data from Balderston et al (see Fig. 2a) 14,16 , which found increases in global connectivity in the intraparietal sulcus during threat-of-shock, suggesting that this region may be a connectivity hub mediating anxiety expression. Accordingly, the goal of the present work was to extract the location within this region with the highest global connectivity.…”
Section: Target Localizationmentioning
confidence: 99%
See 2 more Smart Citations
“…To calculate APS, we subtracted the response during the neutral ITI from the response during the unpredictable ITI. This approach has been traditionally used by our group and was chosen because it allows a direct comparison to other non-NPU threat studies where neutral and predictable blocks are presented without cues (e.g [1,31]). Another benefit to this approach is that the APS measurement is not contaminated by the cue presentation, which can potentiate the startle response even though it does not carry any predictive information about the shock in the U condition [6].…”
Section: Electromyographymentioning
confidence: 99%